Exploring the Use of AI in Qualitative Data Analysis: Comparing Manual Processing with Avidnote for Theme Generation - S. M. Akramul Kabir; Fareeha Ali; Rana Lotfy Ahmed; Ruqayya Sulaiman-Hill (International Journal of Qualitative Methods)
This paper examines the potential benefits and limitations of using Artificial Intelligence (AI) technology in qualitative research. Avidnote, an AI platform designed for research, is compared with manual analysis methods for theme generation. The findings show that Avidnote provides fast theme generation, resulting in significant time and cost-saving benefits. However, both similarities and differences between human and Avidnote-generated themes were observed, raising some concerns regarding the internal validity of AI-generated themes compared to traditional manual analysis. Avidnote can be a valuable supplementary tool in the analysis phase of research, as it has the potential to increase efficiency, reduce bias, reveal subtle themes, and help to compare and contrast themes. However, fundamental concerns persist regarding the robustness, generalisability, credibility, reliability and trustworthiness of qualitative research when using AI technologies. Ethical considerations, such as data security and privacy, also need to be addressed in research settings. AI platforms should not be considered a substitute for critical thinking and personal interpretations, as these are unique skills inherent to humans. Researchers must maintain their fundamental role in determining research objectives and interpreting qualitative data to ensure methodological rigour. Future iterations of Avidnote are likely to address current challenges as advancements in AI continue to evolve. Further research is recommended to assess AI tools tailored for research purposes.